Pengaruh Konsumsi Perasan Kunyit Terhadap Rasa Nyeri Pada Penderita Gastritis Akut Usia 30 – 40 Tahun di Kelurahan BT IX Wilayah Kerja Puskesmas BT X - Chintara Wanda, Aulia; Novia Yanti, Masyitah; Rahardiantini, Ikha; Amarudin, Amarudin (NHM PRESS, 2024)
Gastritis is the most common disease complained of by the public and is a disease that is often found in clinics or internal medicine polyclinics, both in adolescents and adults. Gastritis is a disease that often recurs so that patients need regular treatment. Gastritis can occur suddenly or gradually. Gastritis or pain in the pit of the stomach is caused by inflammation that occurs in the gastric mucosa. Cases of gastritis cannot damage the stomach permanently, but gastritis sufferers often complain of repeated relapses. Based on data on gastritis incidents and research stating the activity of turmeric to overcome heartburn in gastritis patients, this study was conducted to determine the effectiveness of turmeric with different methods and samples. This study also uses variations in dosage which are expected to provide good results and show the effectiveness of turmeric in helping to reduce heartburn so that it can be an adjunct therapy in pain therapy caused by gastritis. Based on this background, a study was conducted to determine whether turmeric (Curcuma longa) has an activity that can help relieve gastritis pain and obtain an effective dose of turmeric juice to help relieve gastritis pain. Data obtained from this study showed that 20 respondents who received turmeric juice before and after the intervention for 1 week showed a significant decrease in pain scale from an average of 7.736842 to 1.263158 (P <0.001) indicating that turmeric juice has been proven to have an effect in reducing the pain scale caused by gastritis. Research shows that turmeric is a non-pharmacological therapy that has great potential to reduce pain scale.